STAT1 is a sex‐specific tumor suppressor in colitis‐associated colorectal cancer. Issue 4 (20th February 2018) - Crnčec, Ilija; Modak, Madhura; Gordziel, Claire; Svinka, Jasmin; Scharf, Irene; Moritsch, Stefan; Pathria, Paulina; Schlederer, Michaela; Kenner, Lukas; Timelthaler, Gerald; Müller, Mathias; Strobl, Birgit; et al.
Abstract : The interferon‐inducible transcription factor STAT1 is a tumor suppressor in various malignancies. We investigated sex‐specific STAT1 functions in colitis and colitis‐associated colorectal cancer (CRC) using mice with specific STAT1 deletion in intestinal epithelial cells (STAT1 ∆IEC ). Male but not female STAT1 ∆IEC mice were more resistant to DSS‐induced colitis than sex‐matched STAT1 flox/flox controls and displayed reduced intraepithelial infiltration of CD8 + TCRαβ + granzyme B + T cells. Moreover, DSS treatment failed to induce expression of T‐cell‐attracting chemokines in intestinal epithelial cells of male but not of female STAT1 ∆IEC mice. Application of the AOM‐DSS protocol for induction of colitis‐associated CRC resulted in increased intestinal tumor load in male but not in female STAT1 ∆IEC mice. A sex‐specific stratification of human CRC patients corroborated the data obtained in mice and revealed that reduced tumor cell‐intrinsic nuclear STAT1 protein expression is a poor prognostic factor in men but not in women. These data demonstrate that epithelial STAT1 is a male‐specific tumor suppressor in CRC of mice and humans. Abstract : The identity of sex‐specific molecular factors in cancer formation and progression remains scarce. We found that the interferon‐inducible transcription factor STAT1 acts as a male‐specific tumor suppressor in colorectal cancer of mice. Moreover, enhanced STAT1 protein expression in tumor cells of human colorectal cancer biopsies is a male‐specific factor for good patient prognosis.